Qualitative Analysis of Consumer Trust and Satisfaction Factors for MSME Products in Online Marketplaces - Muhamad Mahfid Ahnan; Alivia Puspitasari; Mohammat Addul Gofar; Andik Setiawan; Afaful Ummah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study aims to provide an in-depth analysis of the dynamics of consumer trust and satisfaction toward SME products in online marketplaces by employing a literature review method with a descriptive qualitative approach. Marketplaces as digital platforms have opened vast opportunities for SMEs to reach wider audiences; however, they also pose significant challenges related to building trust in a fully virtual interaction environment and sustaining consumer satisfaction amid intense competition. This study draws upon a range of academic sources, particularly SINTA-indexed journals, that are relevant to issues of trust, satisfaction, and digital consumer behavior. The findings reveal that consumer trust is primarily shaped by factors such as product information transparency, transaction security, seller credibility, and service consistency. Meanwhile, consumer satisfaction is largely influenced by product quality, delivery speed, after-sales services, and the overall shopping experience facilitated by the marketplace system. Trust and satisfaction are found to be closely interrelated, with trust serving as the foundation for sustaining long-term satisfaction. These two dimensions not only encourage repeat purchases but also foster consumer loyalty and generate organic promotion through reviews and electronic word of mouth. The study offers practical implications for SMEs and marketplace operators to prioritize strategies grounded in trust and satisfaction as the core of digital business management. Furthermore, its theoretical implications highlight the importance of enhancing digital literacy and consumer protection in order to establish a sustainable, competitive, and healthy e-commerce ecosystem.